Sustainable use of local fodder grasses: a case study from Mayurbhanj district of Odisha - Sahoo, Akshaya K.; Barik, Kamal L. (Ethnobotany Research and Applications, 2025)
Background: Indigenous knowledge of grasses as livestock feed plays a vital role in maintaining sustainable agricultural practices and preserving biodiversity. This research investigates the diverse uses of wild grasses as fodder in the Mayurbhanj district of Odisha, India, exploring their prioritization and the factors influencing their selection. Methods: A thorough ethnobotanical survey was conducted among 198 participants, employing semi-structured interviews and pairwise ranking exercises. Data analysis utilized the Relative Frequency of Citation (RFC) and Pairwise Comparison (PWC) methods. Results: The study identified 67 grassland taxa, spanning 35 genera, used as livestock fodder, with Cynodon dactylon and Oryza sativa emerging as the most preferred species. RFC values ranged from 0.99 to 0.09, with 34 species exhibiting high priority. The correlation analysis among respondents revealed a strong consensus on fodder grass species, with significant positive correlations (RFC = 0.81, p < 0.01 and RFC = 0.69, p < 0.05) indicating shared knowledge and consistent ranking patterns. Furthermore, the priority level of fodder grasses was significantly correlated with their commonality, suggesting that prevalent species are often considered most important for livestock use. Conclusions: This research underscores the importance of wild grasses as a fodder source and highlights the significance of indigenous knowledge in sustainable livestock practices. The findings suggest that conservation efforts should focus on high-priority species and implement community-based initiatives to protect these valuable resources. Keywords: Wild grass, Fodder, Livestock, Mayurbhanj, Odisha